Introdução ao estudo dos números complexos e sua aplicação nos circuitos elétricos - CHUQUILÍN CABANILLAS, Segundo Aurelio (2016)
This dissertation was prepared in order to provide subsidies to mathematics teachers to improve the performance of high scholl students of Y Bacanga college of the State of Maranhãao, specifically the students of three years in math discipline, subject refers to the study of complex numbers. The main idea is to use the Geogebra software and using the various features that the software offers facilitate student learning, and motivate their participation in the classroom, making reference to the theory of complex numbers is used in the study and analysis of electrical circuits. Thus, it presents a brief history of advancing the theory of complex numbers and how the structure was completed, using the Geogebra we study their different forms of representation and its operations are carried out, it shows how subject of complex numbers are used in the study of electrical circuits with emphasis on alternating current AC, solving practical exercises and finally it present a basic concept regarding the way to estimate the power electric consumption in a residence.